EVALUASI DAN PERBAIKAN GEOMETRI JALAN PADA RUAS JALAN MAGELANG – YOGYAKARTA KM 22 –22,6 - Prima Romadhona (TEKNISIA, 2016)
Transportation is an activity or process to moving people or goods from one place to another. Nowadays, with the modern of transportation makes human activity will be more dynamic. Magelang – Yogyakarta street km 22 – km 22,6 is a national road that connect Yogyakarta province with Central Java. The location is a combination of two curves in different opposite direction. The purpose of the research was to evaluate the geometric condition compared from Bina Marga standard. The research method was using direct measurement of actual geometric condition, include horizontal and vertical curve, lane and roadside width using theodolith measuring instrument. Further analysis done by Bina Marga standard. The result that did not met the standard need to be repair geometrically. Analysis result showed that some lane and roadside width section did not met standard of radius by Minister Regulation of Public Works No. 19. Furthermore, all of vertical horizontal did not met standard of minimal length required by National Standardizations Agency. Thus, it needed to repair the horizontal curve by combining previous two curves of B and C based on standard requirement from National Standardizations Agency, that is 120 meter for speed plan 70 km/hours.